Enhancing the capacity of national scientists to generate and transfer maize technology in West and Central Africa: research implementation, monitoring and evaluation - Badu-Apraku, Baffour; Fakorede, M.A.B.; Menkir, A.; Marfo, K.; Akanvou, L. (Cambridge University Press, 2005)
The West and Central Africa Collaborative Maize Research Network (WECAMAN) was established in 1987 to strengthen the capacity and capability of national programmes of West and Central Africa (WCA) to tackle regional constraints to maize production. The Network created several mechanisms for implementing, monitoring and evaluating maize research and development activities, including research project development and implementation, attendance and quality of paper presentation at technical conferences organized by the Network, scientific monitoring tours, consultation visits, mid-term reviews, and end-of-project reviews and impact assessment. WECAMAN's approach to the system of allocating research responsibilities and competitive grants resulted in increased research efficiency and the generation of sustainable technologies that have catalysed increased maize production in the region.